DIURNAL AND ANNUAL VARIATION OF LOW LEVEL CLOUDS IN INDONESIA - Yusuf Afandi, Muhammad
Indonesia is an arhcipelago country located in the tropic region that has complex weather system. This study is conducted to understand the durnal and annual variation of low level clounds at 10meteorological observation stations in Indonesia and to find out the effect of the difference of stations’s elevation to the variation..The counting of low level clouds frequency have been conducted to 15 years of observation data from 2001-2015 in form of synop reports. Moreover, MTSAT imagery from IR 1 for same period also used to understand the cloud’s spatial pattern in Indonesia’s territory. The result shows that annual variations of low level clouds in Indonesia have similar pattern to rainfall pattern of the observation stations. Furthermore, analysis from the comparison of diurnal and annual variation of lowlevel clouds in lowlands and highlands did not shows significant effect. However, according to further analysis it was found that the distance between meteorological observation stasion and coastline give significant impact to the annual variation of the low level clouds, the closer observation station to coastline the greater the difference between maximum and minimum of accumulated frequency of low level clouds occurence. The most frequent low level clouds were formed with base height of 0 – 600 m above the ground. Low level clouds with base height more than 1000 m were rarely found.